(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The present investigation was conducted to assess the water quality status of the river Buriganga. Water samples were collected from three selected stations in wet (June-August) and dry (November-January) seasons during the years 2017 and 2018. Temperature and Dissolved Oxygen (DO) of water varied from 22.80 to 31.40 °C and 0.22 to 2.74 mg/L, respectively. Electrical conductivity of water varied from 180 to 598 μS/cm while pH ranged from 7.61 to 8.97. This study showed that temperature, DO and Fe were higher in wet season than in the dry season, whereas pH, conductivity and phosphate were higher in dry season than in the wet season. But manganese did not vary in different seasons. It is found that the differences of water quality parameters were significant in seasons (p<0.05) except for Fe and insignificant for stations (p>0.05) except for DO. The results reveal that there were significant differences between sampling seasons (wet and dry) (p<0.05) except for temperature and manganese. A significant correlation (p<0.01) was also found among temperature and other parameters viz. DO, conductivity, pH, phosphate. According to the result obtained in the present study, it may be said that the water quality of the river Buriganga is not acceptable to declare the river-ecosystem as a sound one ecologically. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(1): 47-54